HB-UWB transmission wavefrom model for wireless body area network - Teawchim, Sanit; Promwong, Sathaporn (My University, 2017)
This paper are presents characteristics of human body-ultra wide band (HB-UWB) transmission model for WBAN. The human body channel is more complex and distinctive than other application. This complex and irregular shapes that cannot be analyzed as a regular Therefore, to understand human body channel is so important. The channels model is classified with body mass index (BMI). The root raise cosine passband waveform is used as UWB transmitted waveform. The body channel transfer functions on human body are measured follow IEEE802.15.6 by using vector network analyzer (VNA) at frequency 3 GHz to 5 GHz. Distortion is important parameter for UWB waveform transmission. It can be fine from path loss model, which show compared of average power loss and peak power loss. The results can be applied to use evaluation channel model on human body.
Keywords: BAN; Friis's transmission formulal; HB; UWB; WBAN